The Performances of Synchronous and Asynchronous Method in Teaching and Learning English - Pratiwi, Jessy Ayu; Rosalina, Nadya; Rodiah, Nursalimah; Ervina, Wiwin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
This article aims to explain the synchronous and asynchronous methods as distance learning methods, especially in learning English. In the background section, the reasons for the current teaching and learning process problems are explained and why synchronous and asynchronous are good learning methods. Next, the method used in this study is described. Then, explained about synchronous and asynchronous in more detail. Last, conclusion as the closing of the journal.